Poverty on the rise: the impact of the COVID-19 lockdown on the informal sector of Gweru, Zimbabwe - Dzawanda, Beauty; Matsa, Mark; Nicolau, Melanie (Wiley, 2022)
The informal sector in Zimbabwe employs more than 80 per cent of the population, whose livelihood strategies are under severe threat because of the COVID-19 lockdown. This paper examines the effects of the lockdown on the informal sector in Gweru. Anchored within the legalist theory of informality, the paper analyses the response of government to the plight of the informal sector in Zimbabwe. A qualitative research design was applied and convenience sampling implemented to select 30 individuals whose livelihood depended on informal cross-border trade, informal transport, forex trading, hairdressing, and street vending. Results reveal that despite many involved in the informal sector having lost their means of survival during the COVID-19 lockdown, the government introduced additional restrictions on this sector, thus almost destroying it. In the absence of government assistance, many have adapted their operations, albeit through illegal activities. The study offers recommendations that may ensure the survival of the informal sector beyond the COVID-19 pandemic. This is important, given that the informal sector is the largest contributor to household income and food security in Zimbabwe.